Dampak Permainan Pakbol Terhadap Perkembangan Sosial-Emosional Anak Usia Dini - Astri Nurhidayati; Istiqomah, Dita Nurul; Khoirun Nisak; Fatna Nur Sholikhah; Triana Putri; Hidayatu Munawaroh (STAI Al-Amin Gersik Kediri Lombok Barat NTB, 2023)
The purpose of pakbol games for early childhood is to make students become children who can recognize themselves, manage and express their emotions, have a brave soul and build healthy social relationships with their friends. This research was conducted at Pertiwi 1 Punggelan Kindergarten. The respondents in this study were children of Pertiwi 1 Punggelan Kindergarten with the aim of providing innovation to the school in building identity with traditional games or national games that can be introduced from an early age. The methodology used is qualitative with data collection using observation, interviews and documentation. After that, it was analyzed using interactive model data analysis techniques. The application of this game is carried out from the child doing hom-pim-pa until it is finished and tidying up the toys again. The results obtained from this study are that the pakbol game activities held are running well in accordance with the characteristics of the independent curriculum and this game as a lesson to develop the social-emotional aspects of early childhood.